Construction principles of antenna arrays for radiomonitoring systems - Щербина, Ольга Алімівна (Science-based technologies, 2020)
The article deals with several methods by which the antenna systems with the interference suppression are constructed. In phase and amplitude-phase methods, interference suppression occurs due to the formation of radiation patterns with zeros in the direction of the angular location of the interference sources. On the other hand, in the amplitude method, interference suppression is achieved by determining the interference at the same EMF phases of the useful signal and compensating it in a mixture of signal and interference. With this approach to compensation methods, antenna system diagrams can be divided into diagrams with spatial filtering of interference and diagrams with compensation of interference voltage. In this paper, generalized principles of construction of monitoring antenna systems using various methods of interference suppression were considered. The functions of detecting the radiation source, observing the radiation field, radiomonitoring of radiation sources and parameters of the radiation field, determining the angular coordinates of the source location and suppressing interference can be implemented both in antenna systems with spatial filtering of electromagnetic interference waves and in antennas with compensation of interference voltage. Adaptive antennas make it possible to detect the useful signal emission against a background of sufficiently strong noise and interference. But the direction finding functions can be implemented in such antennas only by introducing additional blocks and algorithms into the system that are not inherent in adaptation methods. Adaptive antenna arrays separate the useful signal by electric beamforming of the radiation pattern with minima in the directions of incidence of electromagnetic interference waves. Antenna systems with filtering and noise suppression can use electrical and mechanical control of the radiation pattern.